Wrist protection in snowboarding - Michel, F. I. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The wrist is the most frequently injured body region among snowboarders. Studies have shown that the risk of sustaining a wrist injury can be reduced by wearing wrist protection (Michel et al., 2013). This article reviews the current state of wrist protection in snowboarding and discuss opportunities and limitations for using wrist protectors to prevent injuries in snowboarding.